Distinct metabolomic and lipidomic profiles in serum samples of patients with primary sclerosing cholangitis - Fererberger, Tanja; Buechler, Christa; Kandulski, Arne; Elger, Tanja; Loibl, Johanna; Schmid, Stephan; Sommersberger, Stefanie; Gunawan, Stefan; Zundler, Sebastian; Huss, Muriel; Bettenworth, Dominik; Kempa, Sally; et al. (Frontiers in Medicine, 2024)
Identification of specific metabolome and lipidome profile of patients with primary sclerosing cholangitis (PSC) is crucial for diagnosis, targeted personalized therapy, and more accurate risk stratification. Nuclear magnetic resonance (NMR) spectroscopy revealed an altered metabolome and lipidome of 33 patients with PSC (24 patients with inflammatory bowel disease (IBD) and 9 patients without IBD) compared with 40 age-, sex-, and body mass index (BMI)-matched healthy controls (HC) as well as 64 patients with IBD and other extraintestinal manifestations (EIM) but without PSC. In particular, higher concentrations of pyruvic acid and several lipoprotein subfractions were measured in PSC in comparison to HC. Of clinical relevance, a specific amino acid and lipid profile was determined in PSC compared with IBD and other EIM. These results have the potential to improve diagnosis by differentiating PSC patients from HC and those with IBD and EIM.